Beginning with Biography Cards: Unlocking Student Potential in Diverse Classrooms - Melissa A Holmes; Paolo Fabre-Merchán; Socorro G. Herrera (The Advocate, 2025)
Teachers serving racially, ethnically, and linguistically diverse communities of learners often struggle to enact instruction that is responsive to their unique backgrounds and lived experiences. This paper introduces Biography-Driven Instruction as an instructional framework for advancing enactment of culturally and linguistically responsive/sustaining teaching. It offers the biopsychosocial history of the learner as construct to support deeper understanding of factors that can influence classroom engagement and student wellbeing. It also explores the sociocultural, linguistic, cognitive, and academic dimensions of the culturally and linguistically diverse student biography, which supports teachers to identify assets and strengths that they can leverage to differentiate instruction and support language development and conceptual understanding. The authors provide an array of student biography cards used by teachers in ESL and EFL contexts to illustrate the flexible and adaptable nature of the tool for gathering insights into students’ multifaceted identities to inform lesson planning and delivery.
Keywords: biography-driven instruction; culturally responsive teaching; culturally relevant pedagogy; culturally sustaining pedagogy; linguistically responsive teaching; English as a foreign language; English as a second language